Examining recruitment strategies and millennial employee selection - Manuaba, Ida Ayu Pradnyani Utami; Darma, Gede Sri (International research journal of management, IT and social sciences, 2021)
The purpose of this study is to look for concrete forms of millennial recruitment and selection strategies. Besides, the purpose of this study is to invite the readers of this study to see what obstacles occur in the strategy of recruitment and selection of Millennial employees. This research was conducted at PT. BPR Lestari Bali. Design This study uses a qualitative approach with descriptive analysis methods. The sample used in this study is based on a purposive sampling technique, namely the determination of samples based on the suitability of certain characteristics and criteria. Data collection techniques used are through observation, interviews, and documentation. The results of this study are to look for concrete forms of recruitment and selection strategies for millennial employees. The actual form of recruitment strategy consists of recruitment preparation, dissemination of job vacancies online, acceptance of applications, and through the Internship program. The results of research on the process of implementing the recruitment and selection strategy at PT. BPR Lestari Bali has been implemented well by the company. Several theories have been applied so that there are not many obstacles or obstacles in the implementation of millennial recruitment and selection strategies.